Pemanfaatan Hierachical Token Bucket Dalam Konsep Jaringan Untuk Pengoptimalan Bandwidth - Tobby Octavianto (Department of Information Technology, Universitas Timor, Indonesia, 2021)
The use of the internet in the office requires stability for employees so that they can work well, it is not uncommon for some parties to use internet services for out-of-office needs for downloads and also social media. The Hierarchical Token Bucket (HTB) method in bandwidth management can solve this problem. HTB is a very structured method of sharing the bandwidth. HTB can be created by configuring the Mikrotik routerboard equipment by creating parent and child parameters and determining the minimum and maximum bandwidth used.